Early Psychosis Intervention : A Culturally Adaptive Clinical Guide - Eric Yu-hai Chen, Helen Lee (Hong Kong University Press, 2013)
It is now just over a decade since the first early psychosis programmes were established in Asia, representing a critical frontier in global early psychosis reform. In the intervening years an increasing number of clinical and research programmes have been developed and flourished in various Asian cities. It is inspiring to see that so many pioneering Asian psychiatrists, psychologists and academic leaders have recognized that prevention and early intervention are key potential strategies in the struggle to reduce the burden of mental illness in our rapidly changing societies and have taken effective action. Quite apart from the human cost, the economic impact of untreated or poorly treated mental disorders is a major threat to happiness and prosperity world-wide. In its 2011 report on the impact of non-communicable diseases, the World Economic Forum has shown that mental illness will equal cardiovascular disease as the major threat to GDP in both the developed and the developing economies over the next two decades (Bloom et al., 2011). This is because mental disorders are the â€œchronic diseases of the youngâ€, with 75% of onsets occurring before the age of 25 years, and most between puberty and the mid-twenties (Kessler et al., 2005). Obviously, this is especially relevant in the developing countries with their young populations and rapidly changing societies.